Effectiveness of a nosocomial infection control education module on knowledge and practice among nurses in public hospitals in Aza’al Region, Yemen - Nasr, Gamil Ghaleb Ahmed (2018)
Introduction: The incidence of nosocomial infection is high in Middle East countries (11.8%), including in Yemen (34%). Good knowledge and practices on infection control measures are important for nurses' adherence to infection control measures, However, Yemeni nurses seem to have lack of knowledge and practices regarding nosocomial infection control measures. Previous study by Sherah showed that only 7.2% and 3.4% of the nurses had a good level of knowledge and practices, respectively. Education and training of nurses are important components of an infection control program. Therefore, the aim of this study was to develop, implement and evaluate the effectiveness of a nosocomial infection control educational module on knowledge and practice among nurses in public hospitals in Aza’al Region in Yemen. Method: A Single-blinded randomized hospital-based trial design was used in this study. Eight public hospitals were randomized to intervention-1 (face-to-face intervention + module), intervention-2 (module only) and waitlist group (no intervention). The study was conducted in three phases: (1) developing the module and instrument and baseline pre-intervention evaluation, (2) implementing the intervention and (3) module evaluation. Delivery of the module was based on Situated Learning Theory (SLT). A pre-validated questionnaire was used to collect the data on demographic characteristics, knowledge and practice of nosocomial infections. Data of knowledge and practice were collected at three points of time, i.e. baseline, immediately after the intervention and 3-months post-intervention. Statistical Package for Social Sciences (IBMSPSS), version 21.0 was used for data analysis. A P-value of less than 0.05 level (two-tailed) with 95% confidence interval was considered significant. General Estimating Equations (GEE) was used to measure between and within-groups differences over time. Results: The results of the current study showed that at baseline, most of the participants (69%) had poor knowledge and more than two third of them (77%) had poor level of practices. There was significant association between the degree of previous in-service training in NIs control measures and the nurses’ knowledge (P=0.004). The results from the comparison between the immediately post-intervention and the three-month post-intervention showed a significant increase in the mean score of knowledge among those who received the intervention-1 (face-to-face intervention + module) and the intervention-2 (module only) as compared to the waitlist group (P<0.001). Likewise, the results showed a significant increase in the mean score of practice among those who received the intervention-1 (face-to-face intervention + module) (P<0.001), but no significant improvement of the immediately postintervention (P=0.06) was found among those who received the intervention-2 (module only). Although it was statistically significant at the three-month postintervention (P=0.02), it was not clinically meaningful because it was =0.11%. Furthermore, the knowledge and practice scores achieved from the immediately postintervention sustained over the three-month post-intervention. Conclusion: The findings of the current study indicate that the intervention-1 (faceto- face intervention + module) was more effective than the intervention-2 (module only) in improving knowledge and practices of Yemeni nurses regarding nosocomial infection control measures. In-service training courses to upgrade and refresh nurses’ knowledge and practices about infection control measures are recommended at a regular basis at least six monthly.